2014
DOI: 10.3390/ijms15057513
|View full text |Cite
|
Sign up to set email alerts
|

The Oligomycin-Sensitivity Conferring Protein of Mitochondrial ATP Synthase: Emerging New Roles in Mitochondrial Pathophysiology

Abstract: The oligomycin-sensitivity conferring protein (OSCP) of the mitochondrial FOF1 ATP synthase has long been recognized to be essential for the coupling of proton transport to ATP synthesis. Located on top of the catalytic F1 sector, it makes stable contacts with both F1 and the peripheral stalk, ensuring the structural and functional coupling between FO and F1, which is disrupted by the antibiotic, oligomycin. Recent data have established that OSCP is the binding target of cyclophilin (CyP) D, a well-characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 149 publications
(193 reference statements)
1
45
0
Order By: Relevance
“…ATP5O has a single histidine residue (H135) that is conserved from yeast to humans (Figure 6I), which has potential to be a pH sensor via its physiologically relevant pK a (Faccenda and Campanella, 2012). This residue is located within the hinge region of ATP5O and lies in one of the lowest surface potential regions on the protein (Antoniel et al, 2014). To probe the role of H135, we mutated this residue to glutamic acid, which cannot be protonated in this pH range, and produced recombinant H135E ATP5O protein (Figure 6D and Figure S6D).…”
Section: Resultsmentioning
confidence: 99%
“…ATP5O has a single histidine residue (H135) that is conserved from yeast to humans (Figure 6I), which has potential to be a pH sensor via its physiologically relevant pK a (Faccenda and Campanella, 2012). This residue is located within the hinge region of ATP5O and lies in one of the lowest surface potential regions on the protein (Antoniel et al, 2014). To probe the role of H135, we mutated this residue to glutamic acid, which cannot be protonated in this pH range, and produced recombinant H135E ATP5O protein (Figure 6D and Figure S6D).…”
Section: Resultsmentioning
confidence: 99%
“…Next, given the primary function of OSCP is to sustain the coupling state of F1FO complex we examined F1FO ATP synthase proton-flow coupling [7, 25] by measuring oligomycin A insensitive respiration on a Clark electrode. Our results showed that nonTg mice displayed remarkably increased oligomycin A insensitive respiration in an age-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical data supporting the role of the F 1 −F o ATP synthase is convincing, although its genetic validation in vivo will be complex, given the integral role of this ETC component in mitochondrial ATP synthesis. Additional components of the multimolecular ATP synthase complex are also being studied as potential regulators of the PTP, and hence as potential targets for antinecrotic drug development (48). …”
Section: Basic Biology Of Oxidative Stress Ros and Mitochondrial Fumentioning
confidence: 99%